Role model stories can increase health professionals' interest and perceived responsibility to engage in climate and sustainability actions - J. Kotcher; N. Badullovich; M. Ahmed; D. De Alwis; E.W. Maibach (Elsevier, 2024)
Background: Climate change is one of the most significant threats to human and planetary health. As trusted sources, health professionals have a unique opportunity to help protect society from the impacts of climate change by educating key publics including policymakers about solutions to climate change, as well as reducing their sector's contribution to climate change by promoting sustainable practices in the workplace. Developing methods to activate health professionals as climate educators and advocates is an important step in activating this opportunity. Drawing on the practice of behavioral journalism, this study tests the effectiveness of role model stories at increasing attitudinal and behavioral engagement of health professionals with sustainability. Methods: Participants in this study (n = 39) were employees of a network of U.S. hospitals and urgent care centers that were subscribed to a sustainability e-newsletter published by the healthcare system. Participants were randomly assigned to a control group that only received the regular newsletter, or a treatment group that received an additional series of emails featuring stories about sustainability role models in their healthcare system. Results: We found that receiving the role model stories increased participant's belief that health professionals have a responsibility to support sustainability efforts and their willingness to receive more information about joining a climate and health advocacy organization, although there were no between-group differences on other dependent variables. Conclusion: This study although limited by a small sample size provides evidence that role model stories can play a role in activating healthcare professionals to participate in sustainability initiatives and advocate for climate and health solutions.